ВНУТРИГРАНИТНЫЕ РЕДКОМЕТАЛЛЬНЫЕ ПЕГМАТИТЫ ЩЕЛОЧНОГРАНИТОВОИ ФОРМАЦИИ КОЛЬСКОГО ПОЛУОСТРОВА. КВАРЦ-ЦИРКОНОВЫЕ ПСЕВДОМОРФОЗЫ - Волошин А.В.; Лялина Л.М.; Савченко Е.Э.; Селиванова Е.А. (My University, 2005)
Thorough investigation of accessory mineralization was carried out for intragranite rare-metal pegmatites recently discovered in alkaline-granite formation at Kola Peninsula. Those pegmatite bodies keep a particular place in the series of rocks - from the mere granites up to hydrothermalites and metasomatites: granites-intragranite rare-metal pegmatites-silexites-exocontact pegmatites-amazonite rand-pegmatites. There are sum-marizing description and brief review of some mineral types, within rich and diverse mineralization of «Tsirkonovoye» pegmatite. Quartz-zircon aggregates with such unusual morphology and very special structure were neither described previously in literature, nor studied in detail. Various types of aggregate are distinguished by their structure. Results of their investigation show that they are some particular pseudomorphs. From the point of their possible formation, they may be treated as products replacing the primary zirconium silicates. Pseudo-morphs with similar composition (quartz+zircon) but different morphology were found previously in raremetal alkaline and subalkaline complexes in Canada and Mongolia and considered as a final stage of replacement after primary elpidite. A pattern of stepwise substitution over the primary zirconium silicate, with formation of an in-termediate phase or several phases (armstrongite, gittinsite), is assumed for quartz-zircon pseudomorphs in «Tsirkonovoye» pegmatite also: most likely, eudialyte was there the primary zirconium silicate.
Keywords: 549.6+552.321.1(470.21)